2009
DOI: 10.1016/j.cell.2009.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Telomeres Resemble Fragile Sites and Require TRF1 for Efficient Replication

Abstract: Summary Mammalian telomeres are associated with shelterin, the telomere specific protein complex that solves the end-protection problem. The telomeric shelterin binding sites, TTAGGG repeats, are maintained by telomerase, which solves the end-replication problem. We report that the TTAGGG repeat arrays of human and mouse telomeres challenge the DNA replication machinery, giving rise to replication-dependent defects that resemble those of the aphidicolin-induced common fragile sites. Conditional gene deletion e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

50
1,052
3
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 870 publications
(1,106 citation statements)
references
References 69 publications
50
1,052
3
1
Order By: Relevance
“…The analysis of metaphase spreads showed that Ft1 kof/kof MEFs exhibit multiple telomeric signals (MTS, also known as fragile telomeres) and sister telomere associations (STA) (Figure 2g–i and Figure S1e). These types of telomere aberrations are considered hallmarks of defective telomere replication (Sfeir et al., 2009). Ft1 kof/kof MEFs showed a small but not statistically significant increase in telomere fusions compared to matched control MEFs.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of metaphase spreads showed that Ft1 kof/kof MEFs exhibit multiple telomeric signals (MTS, also known as fragile telomeres) and sister telomere associations (STA) (Figure 2g–i and Figure S1e). These types of telomere aberrations are considered hallmarks of defective telomere replication (Sfeir et al., 2009). Ft1 kof/kof MEFs showed a small but not statistically significant increase in telomere fusions compared to matched control MEFs.…”
Section: Resultsmentioning
confidence: 99%
“…To confirm this phenotype we immunostained the spreads with antibody against TERF1 (Supplementary Figure S6). TERF1 protein binds to repeats in telomeres and protects them against the degradation (79). We found the appearance of clusters of TERF1 clusters in places of telomere connections in ATZ-derived samples.…”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed that these characteristics have important ramifications for human chromosome stability during DNA replication and for integration of mobile DNA elements (46). Being able to engineer hybrid yeast-vertebrate type telomeres in a genetically tractable system should allow us to further detail those evolutionary important mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence obtained in a variety of systems, including budding yeast, fission yeast, and mammalian cells, strongly suggests that the passage of the replication fork through telomeric repeats is a challenge and requires the presence of telomere repeat binding proteins and specialized helicases (45)(46)(47)(48). It has been proposed that these characteristics have important ramifications for human chromosome stability during DNA replication and for integration of mobile DNA elements (46).…”
Section: Discussionmentioning
confidence: 99%